The Effectiveness of Interactive Games for Improving Eighth-Grade Students' Vocabulary Mastery at MTs Alkairaat Alindau - Hizra Amanda; Darmawan Darmawan; Desrin Lebagi; Jamiluddin Jamiluddin (MASI Mandiri Edukasi, 2025)
This study was motivated by the students' limited vocabulary mastery in learning English. Therefore, the researcher applied interactive games as an instructional tool to support students in expanding their vocabulary. The purpose of this study was to investigate the effectiveness of interactive games in improving the vocabulary achievement of eighth-grade learners at MTs Alkhairaat Alindau. The study employed a quantitative approach with a pre-experimental one-group pre-test and post-test design. The participants consisted of 24 students from Class VIII A. The data, collected through pre-tests and post-tests, were examined using a normality test and a paired sample t-test in SPSS software. Findings show that the students' mean score increased significantly from 45.67 in the pre-test to 66.58 in the post-test. The statistical analysis yielded a t-value of -15.668 (with a very large effect size, Cohen's d = 1.48) and a significance value (two-tailed) of 0.000. Since this value is less than 0.05, the null hypothesis (H0) is rejected while the alternative hypothesis (H1) is accepted. Therefore, the use of interactive games such as word matching and crossword puzzles proved effective in significantly improving students' vocabulary mastery at MTs Alkhairaat Alindau. This finding suggests that interactive games can serve as effective alternative strategies in EFL vocabulary teaching, particularly in similar junior high school settings.